Lovesick blues eaudiobook The life of hank williams. - Hemphill, Paul (Recorded Books Inc., 2006)
A sickly and awkward boy who turned into a country music legend, Hiram Williams had reinvented himself as Hank Williams and taken to alcohol by the age of 14. He was dead by the age of 29. Here, Paul Hemphill recounts the tortured life and whirlwind career of the hillbilly Shakespeare as only a fellow Southerner can. " . this is the finest work of literature about Williams yet written."-Booklist